Erythropoietin and its Carbamylated Derivative Prevent the Development of Experimental Diabetic Autonomic Neuropathy in STZ-Induced Diabetic NOD-SCID Mice - Schmidt, Robert E. (2007)
Autonomic neuropathy is a significant diabetic complication resulting in increased morbidity and mortality. Studies of autopsied diabetic patients and several rodent models demonstrate that the neuropathologic hallmark of diabetic sympathetic autonomic neuropathy in prevertebral ganglia is the occurrence of synaptic pathology resulting in distinctive dystrophic neurites (“neuritic dystrophy”). Our prior studies show that neuritic dystrophy is reversed by exogenous IGF-I administration without altering the metabolic severity of diabetes, i.e. functioning as a neurotrophic substance. The description of erythropoietin (EPO) synergy with IGF-I function and the recent discovery of EPO’s multifaceted neuroprotective role suggested it might substitute for IGF-I in treatment of diabetic autonomic neuropathy. Our current studies demonstrate EPO receptor (EPO-R) mRNA in a cDNA set prepared from NGF-maintained rat sympathetic neuron cultures which decreased with NGF deprivation, a result which demonstrates clearly that sympathetic neurons express EPO-R, a result confirmed by immunohistochemistry. Treatment of STZ-diabetic NOD-SCID mice have demonstrated a dramatic preventative effect of EPO and carbamylated EPO (CEPO, which is neuroprotective but not hematopoietic) on the development of neuritic dystrophy. Neither EPO nor CEPO had a demonstrable effect on the metabolic severity of diabetes. Our results coupled with reported salutary effects of EPO on postural hypotension in a few clinical studies of EPO-treated anemic diabetic and non-diabetic patients may reflect a primary neurotrophic effect of EPO on the sympathetic autonomic nervous system, rather than a primary hematopoietic effect. These findings may represent a major clinical advance since EPO has been widely and safely used in anemic patients due to a variety of clinical conditions.